Tasks For Increasing The Effectiveness Of Spiritual and Educational Activities - Turobova Zulfizar Ulug’bek qizi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article analyzes the role and responsibilities of propagators in increasing the effectiveness of spiritual and educational activities. It discusses the importance of spiritual upbringing, methods and techniques for improving the effectiveness of propagators, as well as their social impact. The research results will be useful in elevating spirituality in society and defining the role of propagators.